Teknik dan prosedur Konseling Pancawaskita dalam Perspektif Multibudaya - Fanzha Erza Nanda Saputra; Rendy Nuril Anwar; Bakhrudin All Habsy (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Pancawaskita Counseling is an eclectic approach in guidance and counseling aimed at understanding and assisting individuals by integrating five key factors: Pancasila, Pancadaya, Lirahid (five life domains), Likuladu (five external forces), and Masidu (five internal conditions of individuals). This approach is designed to address challenges in counseling services within a multicultural environment like Indonesia, which is characterized by cultural and social diversity. The techniques used in Pancawaskita Counseling include client acceptance, reflection of content and feelings, as well as specific methods such as lifestyle analysis and role-playing. This study employs a literature review method, which involves collecting data from various reliable sources, reading, taking notes, and analyzing information using a descriptive approach. The purpose of this study is to provide a comprehensive understanding of the concepts, techniques, and procedures in Pancawaskita Counseling and to evaluate its strengths and weaknesses. The findings indicate that Pancawaskita Counseling offers flexibility in adapting counseling methods to clients' needs. However, its application remains limited due to a lack of understanding and minimal development in the field.